Basic Education in Islamic Education (Study of Surah Taha Verse 14) - Soleh, Warissuddin; Jamil, Helmun; Lestari, Agus (Indonesian Journal of Islamic Education and Local Culture, 2023)
The main goal of Islamic education is to give birth to a whole generation. One effort to realize this goal is to understand the basics of Islamic education. This research examines the basics of Islamic education in terms of the main guidelines and basis of Islamic education, namely the Qur'an. The focus of the research is Surah Taha, verse 14. The research approach is qualitative, using library research methods. The data analysis technique uses the Miles and Huberman data analysis model. The result of the research is that there are four basic educations in Islamic education: faith education, worship education, prayer education, and remembrance education. The methods of imparting basic education are prayer, patience, example, practice, and habituation. Tujuan pendidikan Islam adalah melahirkan generasi paripurna. Salah satu upaya untuk mewujudkan tujuan tersebut adalah memahami pendidikan dasar dalam pendidikan Islam. Penelitian ini mengkaji tentang pendidikan dasar dalam pendidikan Islam ditinjau dari pedoman dan dasar pokok pendidikan Islam, yaitu al-Qur’an. Fokus penelitian adalah surat Taha ayat 14. Pendekatan penelitian adalah kualitatif dengan metode penelitian pustaka. Teknik analisis data menggunakan model analisis data Miles dan Huberman. Hasil penelitian adalah terdapat empat pendidikan dasar dalam pendidikan Islam, yaitu pendidikan iman, pendidikan ibadah, pendidikan salat, dan pendidikan zikir. Metode menanamkan pendidikan dasar adalah doa, sabar, keteladanan, latihan, dan pembiasaan.